The Role of Lung Ultrasound in Viral Lower Respiratory Tract Infections - Yousef, Nadya; De Luca, Daniele (American Journal of Perinatology, 2018)
Despite being a bedside technique under rapid development and diffusion, lung ultrasound has not been often used in the management of viral low respiratory tract infections, although these infections represent a significant burden of care in neonatology and pediatrics. The aim of this article is to review the lung ultrasound findings and the evidence-based data available on this topic. Guidance on bedside imaging interpretation and future research direction are also discussed in this article.
Keywords: lung ultrasound; pneumonia; viral infection; children; infants; neonates